Association of dietary n - 3 polyunsaturated fatty acids with breast cancer risk: Serial mediating roles of erythrocyte n - 3 polyunsaturated fatty acids - Zhang, Zhuolin; Jiang, Yiling; Li, Xue; Shi, Dandan; Ma, Ting; Zhou, Ruolin; Zhang, Caixia (Frontiers in Nutrition, 2022)
Background: Dietary n-3 polyunsaturated fatty acids (PUFAs) were found to be inversely associated with breast cancer risk; however, the underlying pathways between them remain uncertain. We aimed to explore serial mediatory roles of erythrocyte n-3 PUFAs in association between dietary n-3 PUFAs and breast cancer risk. Methods: Using a case-control study, 850 cases and 861 controls completed structured questionnaires with dietary information. Erythrocyte n-3 PUFAs were measured by gas chromatography. Odds ratios (ORs) and 95% confidence intervals (CIs) were obtained using multiple unconditional logistic regression models to examine association between dietary n-3 PUFAs and breast cancer risk. Mediation analyses with bootstrapping were conducted to investigate indirect effects. Results: Higher intake of dietary ALA, long-chain n-3 PUFAs and total n-3 PUFAs was associated with lower risk of breast cancer. The adjusted OR tertile 3 v.1 (95% CI) was 0.69 (0.55, 0.88) for ALA, 0.78 (0.6, 0.99) for long-chain n-3 PUFAs and 0.74 (0.58, 0.94) for total n-3 PUFAs, respectively. Mediation analysis showed that erythrocyte long-chain n-3 PUFAs served as sequential mediators in the relationship between dietary long-chain or total n-3 PUFAs and breast cancer risk. In particular, erythrocyte long-chain n-3 PUFAs completely mediated the association between dietary long-chain n-3 PUFAs and breast cancer risk [indirect effect (95% CI)) = -1.027, (-1.578, -0.546)]. The relationship between dietary total n-3 PUFAs and breast cancer risk was partly mediated by erythrocyte long-chain n-3 PUFAs [indirect effect (95% CI) = -0.110 (-0.218, -0.013)], accounting for 20.04%. However, the serial mediation model in dietary ALA and risk of breast cancer was not statistically significant [indirect effect (95% CI) = -0.042 (-0.414, 0.050)]. Conclusion: This study highlights the complexity and inaccuracy in using a simple analysis of individual dietary n-3 PUFAs to examine their associations with breast cancer risk without considering the variety of metabolic processes. Interventions aimed at increasing erythrocyte long-chain n-3 PUFAs may represent a promising strategy for breast cancer prevention.